KONSEPTUALISASI MEDIA PEMBELAJARAN TAJWID INTERAKTIF BERBASIS GOOGLE SLIDES PADA MATERI NUN SUKUN DAN TANWIN - Mahdalena; Nurmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT The development of digital technology has driven a transformation in the learning process, including in Islamic Religious Education. One of the challenges in learning tajwid is students' low understanding of the rules of recitation, which require mastery of concepts and practical skills simultaneously. The material of nun sukun and tanwin is an important basic material in tajwid learning because it forms the basis for reading the Qur'an according to the correct rules. This article aims to examine the conceptualization of interactive tajwid learning media based on Google Slides on the material of nun sukun and tanwin. This study uses a library research method by analyzing various literature related to learning media, digital learning, Google Slides, and tajwid learning. The results of the study indicate that Google Slides has the potential as an interactive learning media capable of integrating text, images, audio, video, animation, and feedback-based evaluation. The conceptualized media consists of a main menu, learning materials, audio reading examples, interactive exercises, and digital evaluation. The use of this media is expected to increase learning motivation, student engagement, and understanding of the rules of nun sukun and tanwin. Thus, Google Slides can be an effective, economical, and easily implemented alternative learning medium for Tajweed teaching in the digital age.